Ever intriguing ‘Primary Amenorrhea’- an audit - Amin, Sapna Vinit; Rai, Lavanya; Palpandi, Priyadharshini; Kumaran, Aswathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Primary amenorrhea though its incidence is less than 0.1% often is a diagnostic challenge in establishing etiology and causes management dilemma to the gynecologist in the developing countries. Methods: A retrospective audit of all the cases of primary amenorrhea coming to our tertiary care teaching hospital in South India over 6 years, from January 2006 to December 2012. Results: Ninety-eight cases of primary amenorrhea were analyzed and it was found that the causes of primary amenorrhea were structural anomalies in 47.9%, endocrinological abnormality in 31.6%, and genetic factors in 20.5% of the patients. Mullerian anomalies were the most common cause for primary amenorrhea compared to gonadal dysgenesis in our study group; hence surgical correction formed an important mode of treatment following diagnosis. Conclusions: Primary amenorrhea work-up may seem to be complex, nevertheless a well elicited history, carefully conducted physical examination followed by use of imaging modalities and bio assays for endocrine abnormalities, permitted the clinician to narrow the diagnostic possibilities and reach an accurate diagnosis quickly that helped in choosing the appropriate management option. While managing, counselling of the patient and her near relatives was very essential for fruitful outcome. Among the surgical approaches for management, sigmoid vaginoplasty was found to be a promising alternative to MacIndoe’s vaginoplasty in our series.